Will Brazilian City Dwellers Actively Engage in Urban Conservation? A Case Study with the Charismatic Neotropical Blue-and-Yellow Macaw (Ara ararauna) - Fabio Angeoletto; Piotr Tryjanowski; Jeater Santos; Beatriz Martinez-Miranzo; Deleon Leandro; João Bohrer; Juciane Maria Johann; Mark D. E. Fellowes (Birds, 2022)
The Blue-and-yellow macaw (Ara ararauna) is a charismatic and easily recognized species. While they are classified as being of “least concern” in the International Union for Conservation of Nature (IUCN) Red List, their populations are declining. In Brazil, the accelerated destruction of one of its key habitats, the Cerrado biome, is a principal cause of their decreasing abundance. As with other species affected by loss of the Cerrado, active conservation measures are required. While usually rare in urban ecosystems, Ara ararauna occurs and breeds in small numbers in the city of Rondonópolis, a medium-sized city located in Mato Grosso, Central-West Region of Brazil. Blue-and-yellow macaw pairs nest in the tops of dead palm trees, but as the macaws are nest-site limited and suitable dead trees are scarce in urban areas, the installation of artificial nest sites in domestic backyards could help that urban population to thrive. To investigate whether local people would be willing to engage with conservation efforts and in particular to support macaw conservation, we surveyed the attitudes of Rondonópolis residents to measure: (1) citizens’ preferences among the bird species that occur in the city; (2) the average area of their yards, and (3) the willingness of residents to: (a) plant fruit trees to attract macaws to their yards and (b) to install artificial nests in their yards. Larger and more colorful birds (Ara ararauna, the Red-and-green macaw Ara chloropterus and Toco Toucan Ramphastos toco) were the bird species most valued across all socio-economic groups, suggesting that the charismatic species would be more likely to be supported by urbanites. Overall, people had good biodiversity knowledge, with respondents being able to identify half of our sample of local bird species, on average, and almost half had seen a nest site. The great majority were willing to plant fruit trees (78%) and provide nest sites (70%) for macaws. This willingness to engage was not affected by socioeconomic differences. These data indicate that a municipal macaw conservation program could be successful in Rondonópolis, and we argue that macaws could be a flagship species which would benefit wider efforts to engage Brazilian urbanites in active engagement with nature.